Autochthons in Tahira Iqbal’s Novel "Girran" - Ansari, Tariq (sourcecoder, 2023)
The influence of regional language and culture is significant in Tahira Iqbal’s novel, Gar’aan. There we can maintain that Pakistan Urdu Novel has the impact of regional language and culture. Due to its cultural and Civilizational aspects, Urdu languages has an ability to absorb new words. Literature presents a true and living picture of any society. Among many genres of literature, Novel outshines because of his characteristic of dealing with the linguistic and cultural material more than any other genre. The language of this novel is entrusting, trustworthiness, credence and identity to the regional discourses and in this process the authentic image of the spirit the Pakistan is manifested.